Rancang Bangun Sistem Informasi Akuntansi Penggajian Karyawan dengan Menerapkan Metode Waterfall - Salsabila, Megaranti; Aditiarno, Ratnanto; Sufyana, Candra Mecca (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Based on research conducted that the Center for Standardization and Services of the Cellulose Industry has fully used a computerized system, namely the Central Civil Servant Salary Application (GPP). However, there are obstacles related to the system where there are often system updates that take a lot of time, thus hampering the salary calculation process. Referring to these problems, this study focuses on improving the employee payroll system that is more optimal and the system is able to provide convenience in controlling employee perfomance activites using the waterfall method. The waterfall method includes 5 stages including system requirements analysis, design, program code generation, testing and support or maintance. The waterfall methors has a sequential process and has a clear and detailed flow, so that unmet system needs will be analyzed indepth to be developed into a system that is in accordance with what is expected and on target. So the final result by applying the waterfall method to the system design made is the processing of employee payroll data more quickly and effectively and helps those who need information as quickly as possible.